1989
DOI: 10.1002/j.1460-2075.1989.tb03393.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the ligand binding site of EGF-receptor utilizing chimeric chicken/human receptor molecules.

Abstract: The epidermal growth factor (EGF)‐receptor is composed of an extracellular ligand‐binding region connected by a single transmembrane region to the cytoplasmic kinase domain. In spite of its importance for understanding signal transduction, the ligand‐binding domain of the EGF‐receptor is not yet defined. We describe the identification of a major ligand‐binding domain of the EGF‐receptor by utilizing chimeras between the human EGF‐receptor and the chicken EGF‐receptor. This approach is based on the fact that mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(116 citation statements)
references
References 21 publications
8
106
1
1
Order By: Relevance
“…The cytostatic effects of decorin correlated with a markedly reduced proliferative index and an attenuation of the EGFR kinase activity both in vitro and in vivo, thus further stressing the important physiological role of decorin in EGFR function. Our findings provide an independent confirmation of previous studies that have used chemical (59,60), immunological (61), and genetic approaches (62) and further refine the mapping of EGF as well as decorin to a discrete region within the L2 domain of the EGFR. Our data raise the intriguing possibility that solidstate signals in the extracellular environment may cooperate or compete with traditional soluble ligands, such as EGF or TGF-␣, to determine the signaling properties of the EGFR in vivo as recently proposed for the EGF-like repeats of tenascin-C (63).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The cytostatic effects of decorin correlated with a markedly reduced proliferative index and an attenuation of the EGFR kinase activity both in vitro and in vivo, thus further stressing the important physiological role of decorin in EGFR function. Our findings provide an independent confirmation of previous studies that have used chemical (59,60), immunological (61), and genetic approaches (62) and further refine the mapping of EGF as well as decorin to a discrete region within the L2 domain of the EGFR. Our data raise the intriguing possibility that solidstate signals in the extracellular environment may cooperate or compete with traditional soluble ligands, such as EGF or TGF-␣, to determine the signaling properties of the EGFR in vivo as recently proposed for the EGF-like repeats of tenascin-C (63).…”
Section: Discussionsupporting
confidence: 88%
“…Fifth, EGF and TGF-␣ bind to a soluble L2 domain with affinities (K D ϭ 400 nM) indistinguishable from those of the soluble EGFR ectodomain (69). Finally, domain-swapping experiments between human and chicken EGFR, implicated both the N-and C-terminal halves of L2 as strong interacting sites (62,70). Thus, L2 contains at least two contiguous regions that together provide most of the interactions that define specificity of EGF to the receptor.…”
Section: Fig 6 Decorin and Egf Bind To A Finite Region Within The Lmentioning
confidence: 98%
“…Multiple studies have concluded that EGF binds EGFR with a 1 : 1 stoichiometry (Brown et al, 1994;Domagala et al, 2000;Lemmon et al, 1997;Odaka et al, 1997;Weber et al, 1984). Subdomains I and especially III of the extracellular portion of EGFR have been identi®ed as important in ligand binding (Lax et al, 1998(Lax et al, , 1989Lee et al, 1995;Summer®eld et al, 1996), as has subdomain IV, one of two cysteine rich domains (Saxon and Lee, 1999). Recent structural modeling proposes that EGF binds in a cleft formed by subdomains I, II and III .…”
Section: Ligand-dependent Dimerizationmentioning
confidence: 99%
“…Anti-ptyr 5E.2 (Fendly et al, 1990) and mAb 108.1 (Lax et al, 1989) are mouse monoclonal antibodies and were kindly provided by A Ullrich. Polyclonal rabbit anti-STAT5b (C-17), anti STAT1(E-23) and anti-ERK2(C-14) were from Santa Cruz Biotechnology, USA.…”
Section: Antibodiesmentioning
confidence: 99%